Linkage Disequilibrium and Effective Population Size of Buffalo Populations of Iran, Turkey, Pakistan, and Egypt Using a Medium Density SNP Array - Rahimmadar, Shirin; Ghaffari, Mokhtar; Mokhber, Mahdi; Williams, John L. (Frontiers in Genetics, 2021)
Abstract Linkage disequilibrium (LD) across the genome provides information to identify the genes and variations related to quantitative traits in genome wide association studies (GWAS) and for the implementation of genomic selection. LD can also be used to evaluate genetic diversity, population structure and reveal genomic regions affected by selection. A set of 58 water buffaloes, comprising AZI, KHU and MAZ breeds from Iran, KUN and NIL from Pakistan, and buffalo from Turkey (ANA) and Egypt (EGY), were used to assess LD structure and calculate Ne. The values of corrected r2 for AZI, KHU, MAZ, three pooled Iranian breeds (IR), ANA, EGY, KUN, NIL and two pooled Pakistani breeds (PAK) populations were 0.26, 0.27, 0.26, 0.24, 0.28, 0.27, 23, 24 and 0.22, respectively. The corrected r2 between the SNPs decreased with increasing physical distance from 100Kb to 1Mb. The LD values for AZI, KHU, MAZ, IRI, ANA, EGY, KUN, NIL and PAK populations were 0.24, 0.25, 0.23, 0.16, 0.23, 0.24, 22, 22 and 0.21 for distance less than 100kb, respectively, which reduced rapidly to 0.048, 0.053, 0.075, 0.018, 0.042, 0.059, 0.074, 0.46 and 0.024, for a distance of 1Mb. In all the populations, the decay rate was small for distances greater than 2Mb up to the longest studied distance (15Mb). Using unrelated samples, the r2 values from adjacent SNPs indicated that SNPs from Affymetrix Axiom 90K SNP genomic array could be used for GWAS and genomic selection in these populations. The Persistency of LD phase (PLDP) between populations was assessed and results showed that PLPD values between all studied populations was more than 0.9 for distances less than 100Kbp. Therefore, it should be possible to use genomic information from some of these populations to predict genetic effects in another.